Joint Land Titling and Household Bargaining in Madagascar. Issue 4 (2nd October 2019) - Widman, Marit; Hart, Robert
ABSTRACT: This paper investigates analytically and through numerical simulations how the intrahousehold bargaining positions of a couple are affected by the opportunity to title agricultural land, and how the couple's choice between an individual male title and a joint title is determined. The results suggest that when land registration is offered to couples as a discrete choice between individual or joint titles, there is a risk that women with weak initial bargaining positions will be further weakened following the reform. A joint title will only be chosen if the spouses start off with relatively equal bargaining positions; otherwise a male title will be chosen. An application of the model to the situation of Madagascar, using household survey data, supports the predictions of the model.